A study of determinants that affect consumer's satisfaction: examination on internet banking behaviour among rural consumers in Selangor / Ain Syamimi Abdul Qawi - Abdul Qawi, Ain Syamimi (Faculty of Business and Management, 2019)
The banking industry has been rapidly developing the use of internet banking as an efficient and viable tool to create customer value. It is one of the popular services offered by most of banks to provide speedier and reliable services to online consumers. However, there are still consumers that are refuse to use internet banking services offered. The issues arose when there are many challenges that need to be face in adoption of these services such as cyber fraud and security risk, high cost of internet facilities and provision of excellent quality service especially in the rural area. This shows that services offered through internet banking have yet to satisfy the consumers. Consumer's satisfaction is an important factor that could assists banks to sustain their competitive advantages. Therefore, the purpose of this research is to investigate the determinants that affect consumer's satisfaction and examines the internet banking behaviour among rural consumers in Selangor. The three determinants which could influence consumer's satisfaction toward internet banking include of service quality, convenience and security. With the use of a questionnaire survey, 1 17 internet banking consumers who lived in rural area in Selangor that participated in this study have provided valuable responses pertaining to the above determinants. The results of this research showed that there is positive relationship between independent variable of service quality and dependent variable which closely linked to consumer's satisfaction towards internet banking as the p-value shows the significant value below 0.005.